CEOs' general managerial skills and corporate risk taking subject to the moderator of CEO tenure - Leng, Tiecheng; Pan, Luyao (European financial management : the journal of the European Financial Management Association, 2023)
In this study, we examine the relation between chief executive officers' (CEOs') general managerial skills and firms' risk‐taking behaviour. We find that generalist CEOs are associated with significantly higher firm risk, with the association decreasing significantly with CEO tenure. We propose the following managerial skills transformation explanation: the longer a CEO stays with a firm, the less general and more firm specific the CEO's skills and knowledge become; therefore, any effect of the CEO's general managerial skills only appears in the early years of tenure.